Mapping education strategies in european context: a survey of teaching-learning approaches, tools and assessment among ENPHE members - Alves Lopes, António (2022)
Purpose The context of education in the health professions has been influenced by the same tendencies of development of knowledge and technology that society faces. It is therefore important that educational institutions are capable of promoting an evolutionary profile of professionals that is adapted to the needs of the future society. Subjects Lecturers from Higher education institutions belonging to the ENPHE Network Material / Methods In the context of the ENPHE group “Facilitation of Learning” and based on the literature, an online questionnaire was constructed regarding teaching approaches. After a pilot study within 5 institutions, the final version of the survey was disseminated during the ENPHE 2018 seminar and until July 2018 by email. Results We had 143 survey responses from 19 country's, most of the respondents were fulltime lecturers (54%) at Bachelor´s level (89%). The responses indicated that the most commonly used Learning Approaches included, Problem Solving (86%) and Content Focus activities (83%) using mainly lectures (78%) and practical training in class (83%) and the most popular tools used were aimed to facilitate retrieving, recalling or recognizing knowledge (97%), The use written (86%) and/or practical examination (77%) as assessment strategies. Conclusions The results still reflect a classic approach to teaching and learning as shown by the selection of approaches, tools and assessment strategies. Educational relevance. The results have provided some insight and also could guide ENPHE devising strategies to facilitate the use of more student inclusive and active learning strategies in Physiotherapy education.